IMPROVING STUDENT READING ABILITY BY SETTING A READING BOOTHS AT MIZANUL ULUM SANROBONE BOARDING SCHOOL - Nureda Rumbaru; Kasma F. Amin; Ihramsari Akidah (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to describe the improvement in students' reading skills by providing reading booths at the Islamic Senior High School Mizanul Ulum Sanrobone. The design of this research is classroom action research. The subjects in this study were students of class XI IPS MA at the Mizanul'ulum Sanrobone Islamic Boarding School. The research results obtained after the implementation of the action, namely students became more active and enthusiastic in participating in learning to read. Students show attitude, interest and high enthusiasm. In addition, there is an increase in students' reading skills which is shown through the reading test results. In the pre-cycle activities of students there were no students who met the KKM standards. The results of the action cycle of one student who met the KKM standard were 15 people or 62.5%. The results of the actions in the second cycle of students who met the KKM standards were 23 or 95.83% of the total number of students. This shows that the existence of a Reading Stall using the classroom action research method can improve students' reading skills.